2022
DOI: 10.1155/2022/5347718
|View full text |Cite
|
Sign up to set email alerts
|

Antileukaemic Cell Proliferation and Cytotoxic Activity of Edible Golden Cordyceps (Cordyceps militaris) Extracts

Abstract: Golden cordyceps (Cordyceps militaris) is a mushroom of the genus Cordyceps. It has been used as a food supplement for both healthy and ill people. In this study, the antileukaemic cell proliferation activities of golden cordyceps extracts were examined and compared with standard cordycepin (CDCP) in EoL-1, U937, and KG-1a cells. Wilms’ tumour 1 (WT1) protein was used as a biomarker of leukaemic cell proliferation. The cytotoxicity of the extracts on leukaemic cells was determined using the MTT assay. Their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We, therefore, further tested whether CD and m 6 2 A could affect ISG20 expression and found that both promoted ISG20 expression at the protein and mRNA levels. CD is a natural active component of traditional Chinese medicine (TCM) fungus cordyceps militaris, which has anticancer properties (33)(34)(35). m 6 2 A is a modified ribonucleoside in the tRNA of mycobacterium bovis, according to Bacille Calmette-Gueŕin (36).…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, further tested whether CD and m 6 2 A could affect ISG20 expression and found that both promoted ISG20 expression at the protein and mRNA levels. CD is a natural active component of traditional Chinese medicine (TCM) fungus cordyceps militaris, which has anticancer properties (33)(34)(35). m 6 2 A is a modified ribonucleoside in the tRNA of mycobacterium bovis, according to Bacille Calmette-Gueŕin (36).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting extracts were filtered through Whatman No. 1 filter paper (Merck KGaA, Darmstadt, Germany) and the solvent pooled from three cycles of maceration was evaporated by a rotary evaporator (Buchi Evaporator, Heidolph, Germany) [43]. The extract was obtained and stored at 4 • C until the next usage.…”
Section: Conventional Solvent Extractionmentioning
confidence: 99%
“…Several active compounds are present in Cordyceps mushrooms, such as ergosterol, mannitol, and modified nucleosides [ 69 ], but the major functional component with medicinal properties shared by both the aforementioned fungi is cordycepin, whose anticancer effects on various tumors, including BC, have been reported [ 63 ]. These antitumoral properties are attributed to structural similarity with cellular nucleosides and adenosine: cordycepin, lacking oxygen at the 3′-position of its ribose moiety, acts like a nucleoside analog and inhibits the polyadenylation of the mRNA of cancer cells [ 65 ].…”
Section: Edible/medicinal Mushrooms In Breast Cancermentioning
confidence: 99%